SOLAR TRACKING-AN OVERVIEW & CHARACTERIZATION - MR. PRATHAMESH D. PATIL; PROF. R. H. MADHAVI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Sun Tracking System for Solar panel project is made to tracking the Sun at day time for using its solar energy appropriately for solar board. The Sun trackers are all climate, dependable and reasonable tracking and situating instruments. This project orients the Solar Panel toward the sun, so it can use with higher precision. Our Sun Tracker framework track the Sun by utilization of sensors and pivot the solar board by method for stepper motor. For level board applications, trackers are utilized to minimize the edge of occurrence between the approaching light and a solar board. This builds the measure of energy created from a settled measure of introduced power producing limit. The optics in concentrated solar applications acknowledges the direct part of sunlight light and thusly should be situated properly to gather energy. Tracking frameworks are found in all concentrator applications in light of the fact that such frameworks cannot deliver energy unless situated nearly toward the sun.